Investigation of ph effect on the performance of undoped silicon carbide nanowire field-effect transistors for the development of chemical sensors and biosensors - TEKER, KAŞİF (My University, 2022)
The effect of pH on the performance of undoped silicon carbide nanowire field-effect transistors (SiCNW-FETs) was systematically studied using various solutions with pH ranging from pH 2 to pH 13 and important transport parameters such as transconductance, mobility, and resistivity were reported. Interestingly, at 2 V, alkaline solutions with high pH value (pH 13) revealed a higher transconductance of 7.13 nS and lower resistivity of 40 omega cm as compared to acidic solutions with 0.01 nS and 2.1x10(4) omega cm at pH 2, respectively. A model describing the pH-dependent conductance of the SiCNW-FETs was proposed. Moreover, a comprehensive comparison of the pH effects on the transport properties of the undoped SiCNW-FETs and nitrogen-doped SiCNW-FET was presented and the measurements clearly revealed opposite trends for a wide range of pH solutions. In short, our SiCNW-FETs with high sensitivity, high stability, and minuscule sample volume can provide solutions for the development of harsh environment compatible nanosensors for chemical, biochemical, and environmental sensing applications.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Fizik; Temel Bilimler; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Signal Processing; Physics; Natural Sciences; Engineering and Technology; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Malzeme Bilimi; FİZİK, UYGULAMALI; Temel Bilimler (SCI); ENGINEERING, ELECTRICAL & ELECTRONIC; ENGINEERING; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE, MULTIDISCIPLINARY; MATERIALS SCIENCE; PHYSICS, APPLIED; PHYSICS; Natural Sciences (SCI); Metals and Alloys; Materials Chemistry; General Engineering; Statistical and Nonlinear Physics; General Materials Science; Engineering (miscellaneous); Electrical and Electronic Engineering; Physical Sciences; pH effect; biochemical sensing; undoped SiC nanowires; SiCNW-FETs; environmental sensing; FABRICATION; pH efect; biochemical sensing; undoped SiC nanowires; SiCNW-FETs; environmental sensing